Principiologia contratual no Estado democrático e social de direito: limites e possibilidades da intervenção Estatal nos contratos - Hallwass, Norberto (Universidade do Vale do Rio do Sinos, 2007)
This study presents through a bibliographical research, by means of a phenomenological analysis, the evolution of the constitutional principles of the contract law. The historical evolution of the development of the state is presented since the manifestation of the city-state of Rome, analyzing the social organization up until then, to the appearance of the Modern State with the French Revolution. Its evolution has still been studied, through the Liberalism ideas, the Social Well-Being until reach the Law Democratic State. The main guidelines of the contracts are presented, accomplishing the analysis of their alterations, in consequence of the State transformations. The present work also presents the Law Democratic State as a guarantee model of paradigms where there is no distinction between public and private, and this way the state intervention in the contract law is considerable, aiming to guarantee the rights inserted in the Constitution. This model preserves the interest of the collectivity in detriment
Keywords: Estado democrático; garantias constitucionais; intervenção estatal; princípios contratuais; Estado liberal; constitutional guarantees; contract principles; democratic State; state intervention; liberal State; Ciências Sociais Aplicadas